Breast cancer associated with pregnancy: a clinical case - Yu E Dobrokhotova; S E Arakelov; S Zh Danelyan; E I Borovkova; A E Zykov; S A Zalesskaya; E A Nagaytseva (IP Berlin A.V., 2018)
Associated with pregnancy is breast cancer, which was first detected during pregnancy, during the first year after childbirth or at any time against lactation. Diagnosis of the disease in the first trimester is an indication for abortion. The detection of the disease after 20 weeks and the desire of the woman to maintain pregnancy is the basis for conducting a total mastectomy followed by polychemotherapy with doxorubicin with cyclophosphamide or with fluorouracil. Radiation therapy during pregnancy is not applied. The timing and method of delivery are determined individually and depend on the stage of the process and the period of pregnancy, when it was identified. A clinical case of a patient with edematous-infiltrative form of breast cancer of the IV stage, diagnosed for the first time in 22 weeks of pregnancy, is presented.